The lifelong impact of fetal growth restriction on cardiac development. (October 2018) - Masoumy, Emily; Sawyer, Alexandra; Sharma, Suash; Patel, Jenny; Gordon, Paul; Regnault, Timothy; Matushewski, Brad; Weintraub, Neal; Richardson, Bryan; Thompson, Jennifer; Stansfield, Brian
Abstract Background Maternal nutrient restriction (MNR) is a widespread cause of fetal growth restriction (FGR), an independent predictor of heart disease and cardiovascular mortality. Our objective was to examine the developmental and long-term impact of MNR-induced FGR on cardiac structure in a model that closely mimics human development. Methods A reduction in total caloric intake spanning pregestation through to lactation in guinea pig sows was used to induce FGR. Proliferation, differentiation, and apoptosis of cardiomyocytes were assessed in late-gestation fetal, neonatal, and adult guinea pig hearts. Proteomic analysis and pathway enrichment were performed on fetal hearts. Results Cardiomyocyte proliferation and the number of mononucleated cells were enhanced in the MNR–FGR fetal and neonatal heart, suggesting a delay in cardiomyocyte differentiation. In fetal hearts of MNR–FGR animals, apoptosis was markedly elevated and the total number of cardiomyocytes reduced, the latter remaining so throughout neonatal and into adult life. A reduction in total cardiomyocyte number in adult MNR–FGR hearts was accompanied by exaggerated hypertrophy and a disorganized architecture. Pathway analysis identified genes related to cell proliferation, differentiation, and survival. Conclusions FGR influences cardiomyocyte development during critical windows of development, leading to a permanent deficiency in cardiomyocyte number and compensatory hypertrophy in a rodent model that recapitulates human development.